Penerapan Lampu Penerangan Jalan Umum Otomatis Tenaga Matahari di Nagari Lagan Mudik Punggasan - Hanalde Andre; Vanzir Firmansyah; Rudy Fernandez; Baharuddin Baharuddin; Rizki Wahyu Pratama; Syaifa Mulyadi (Warta Pengabdian Andalas, 2023)
Street lighting is needed to ensure road users' smooth running and safety. Lack of light will create a high risk of accidents and crime on the road. Many areas in Indonesia in general and West Sumatra in particular, mainly rural areas, still need street lighting due to the need for regional capacity to provide lighting on public roads. This activity implemented street lighting in Nagari Lagan Mudik Punggasan, Linggo Sari Baganti District, Pesisir Selatan District, West Sumatra Province. A total of five light units have been installed in four different locations. Installation of lights using a pole made of wood as high as 4 meters on the 20 KV distribution electricity post and the welcome board of the village. The lights work automatically and can be active when dark and off when bright. The lamp's working principle utilises solar panels, which produce electricity during the day. The source of electrical energy used by the light comes from a battery that a solar panel has charged. This system is expected to overcome the village's lack of street lighting and use clean, environmentally friendly energy sources.